ANALISIS PENDING KLAIM BPJS GUNA MENUNJANG KELANCARAN KLAIM JKN DI RSAU LANUD SULAIMAN BANDUNG - Pujilestari, Intan; Monica, Rizqy Dimas; Indriyani, Rina (Jurnal TEDC, 2023)
Health services as a sub-component of the national health system that have direct contact with the community. In order to realize good and quality health services, the government is responsible for the implementation of public health insurance through the National Health Insurance through claims pending or delayed claims from the BPJS to the hospital. In July to September there were pending claims of 68 out of 1912 files resulting in delays in payment of Rp. 83,561,200. The purpose of this study is to find out the pending BPJS claims to support the smooth running of JKN claims at the Sulaiman Air Force Hospital in Bandung. The research method used is descriptive method with a quantitative approach. Data collection techniques used are observation, interviews and documentation studies. The population in this study is the pending BPJS claim files for 2021, with a sample of 211 outpatient pending files and 80 inpatient files. The sampling technique is saturated sampling. The results of the author's research, there is no written SOP regarding the implementation of claims at the hospital. The sample of pending BPJS claim data on outpatient care was 211 (3%) from 7016 files and inpatient care was 80 (10.16%) from 787 files. The occurrence of pending claims will affect the smoothness of the conformity of the payment amount submitted to the JKN. The average suitability of payment of outpatient claims was 96.8% and 89.84% for inpatient care. The cause of pending is due to coding, medical, and administrative factors. The author's conclusions and suggestions are that there is no written SOP regarding the implementation of claims, it is better to make a procedure for implementing claims in writing. Pending claims occur due to incomplete claim requirements so that they can hinder the smooth payment of claims submitted. It is better to conduct socialization and regular meetings to all relevant parties regarding claim procedures and claim settlement.